The prototype of mobile application for dyslexic children in writing skill ability (CinTA) / Wan Norazlin Wan Azman - Wan Norazlin, Wan Azman (2016)
This research is about developing the mobile application for dyslexic children that having writing skill ability between ages 5 years to 10 years. This mobile application was choosing Android as the main platform because the ratings of user that use mobile phone in Android platfonn are rapidly increased. The dual coding theory has been implemented in this project because dyslexic children use the right brain to learn and understand something that make them confuse. When a lot of multimedia component be added in this application, it totally can get 100 % of dyslexic children interestBasically, the writing skill ability of dyslexic children is chosen because the writing skills are important part before the children being able to writing and reading. A dyslexic child has to know the alphabetic knowledge first before start to next step. The alphabetic knowledge means how the structure of the alphabet, what are the name of the alphabet, how to identify the alphabet and others. The writing skill ability will chose as the main ability problem and the alphabetic knowledge will be focused because it related with the problem that has been discussed. Puan Nor Hayati Ismail, a teacher that teach dyslexic children in SK Sultan Ahmad Tajuddin has been used the wonderful technique to dyslexic children to overcome the alphabetic knowledge problem. This technique will be applied in this mobile application due to the awareness to share this technique to the society. For the future work, the databases that can keep children score and add more module is being suggested. The more interactive and module being added can make the children more enjoying to do it.